Book use in the U.P. Statistical Center Library a bibliometric study - Javier, Victoria Linda B.; Umila, Benwardo V.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1987)
This is a study on book use applying the Morse-Chen Model to determine book ciculation characteristics of the Statistical Center Library, University of the Philippines Diliman. Using probability theory, the model can obtain unbiased estimates of book circulation and predict future circulation behavior.
The check-out sampling method was followed. Data was collected from July 21, 1986 to August 16, 1986. The basic sampling unit was the book card. The book's circulation history for a six year period was collected. Book cards recording observations for six years were separated from newer cards recording observations for less than six years.
The results indicate that: 1) the Morse-Chen Model is applicable to a special collection with less than ten thousand volumes; 2) the circulation estimates obtained by the study are: a) twenty-two percent of the circulating book collection of the library is active; b) two-thirds of the circulating book collection is inactive or very seldom used; c) the estimated yearly circulation is 2.954; d) the predicted circulation for next year is 3.368; 3) the value of parameter alpha which measures the asymptotic circulation is 1.85 for the active books and 1.31 for the active and potentially active books, indicating that recently acquired books circulate more than older books; and 4) the average circulation of the active and potentially active books is two circulations per book per year.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Bibliometrics; Libraries--Circulation, loans